Kajian Hukum Penanganan Anak Yang Melakukan Penyalahgunaan Narkotika - Hendra Bavo Sembiring; Ediwarman Ediwarman; Isnaini Isnaini (Mahesa Research Center, 2022)
The purpose of this study was to examine and analyze the legal rules regarding the handling of children who commit criminal acts, the factors that cause narcotics abuse and the policies taken by the Directorate of Drug Investigation of the North Sumatra Regional Police in Handling children who abuse narcotics. This research relies on secondary data sources consisting of positive criminal law legislation in Indonesia, namely the Criminal Code, laws and regulations outside the Criminal Code relating to problems, the 2008 National Criminal Code Concept, the Child Criminal Justice System, various laws and regulations obtained from various countries as material for comparison as well as various opinions of legal experts that are closely related to this research. The results of the research state that the legal rules regarding the handling of children are regulated in the SPPA Law No. 11 of 2012, where in the law that the handling of children must prioritize the protection of children. The factors causing narcotics abuse by children in the Legal Area of the North Sumatra Regional Police are: lack of parental supervision, follow-up factors, intentionally being used by narcotics dealers, narcotics trafficking which is getting out of control until it is very close to the social environment of children. everyday life, as well as the lack of children's understanding of the dangers of narcotics. Policies for handling children who commit criminal acts of narcotics abuse in the North Sumatra Regional Police are guided by the SPPA Law No.11of2012.